2022
DOI: 10.1108/jfbm-03-2022-0045
|View full text |Cite
|
Sign up to set email alerts
|

Strategic responses of the family businesses in accommodation industry: lessons for overcoming crises

Abstract: PurposeThe purpose of this study is threefold: 1) to examine the relevance of specific strategic orientations for family businesses in the context of an intense crisis such as the COVID-19 pandemic; 2) to investigate the role of a family adaptability in surviving the crisis; and 3) to assess how proactive strategic responses connected with marketing or retrenchment responses connected with reducing costs relate to the expected survival of the crisis.Design/methodology/approachThe method adopted is a quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 137 publications
(478 reference statements)
0
11
0
Order By: Relevance
“…Many studies in our review measured resilience as an outcome (e.g., Acquaah et al, 2011; Bürgel et al, 2023) and operationalized it as financial performance (typically compared to non-family businesses) (e.g., Brunelli et al, 2023; Minichilli et al, 2016). Only a few studies looked at other resilience outcomes, such as innovation, survival, and longevity (e.g., Crespo et al, 2023; Randolph, Memili, et al, 2022; Stafford et al, 2010, 2013). In future resilience research on family businesses, it is crucial to delve deeper into key outcomes of demonstrated resilience that are central to, and idiosyncratic for, the unique organizational form of family businesses and long-term oriented objective of passing on a healthy business to the next generation (Lumpkin et al, 2010).…”
Section: Discussion and Agenda For Future Researchmentioning
confidence: 99%
“…Many studies in our review measured resilience as an outcome (e.g., Acquaah et al, 2011; Bürgel et al, 2023) and operationalized it as financial performance (typically compared to non-family businesses) (e.g., Brunelli et al, 2023; Minichilli et al, 2016). Only a few studies looked at other resilience outcomes, such as innovation, survival, and longevity (e.g., Crespo et al, 2023; Randolph, Memili, et al, 2022; Stafford et al, 2010, 2013). In future resilience research on family businesses, it is crucial to delve deeper into key outcomes of demonstrated resilience that are central to, and idiosyncratic for, the unique organizational form of family businesses and long-term oriented objective of passing on a healthy business to the next generation (Lumpkin et al, 2010).…”
Section: Discussion and Agenda For Future Researchmentioning
confidence: 99%
“…Hence, given this limited understanding of religion in crisis management and the heterogeneity of FFs, qualitative research is crucial for developing insights and advancing FF research (Reay, 2014;De Massis and Kammerlander, 2021). Qualitative research provides additional insights into crisis management (Byrne and Shepherd, 2015) and addresses the complexity of FFs (De Massis and Kammerlander, 2021), complementing the majority of quantitative research (Çetin, 2021;Crespo et al, 2023). Therefore, following recent studies (Lepp€ aaho and Ritala, 2022; Mitter et al, 2022), we adopt a qualitative and interpretative approach to gather rich data (De Massis and Kotlar, 2014;Nordqvist et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Early evidence by Kraus et al (2020) shows that FFs are able to respond quickly by adapting their business models and using digital technologies to optimize their business processes. Further studies show that FFs change their organizational behavior and enhance their adaptive capacity (Soluk et al, 2021;Crespo et al, 2023), can adopt effective crisis management practices and maintain stakeholder trust (Mitter et al, 2022). FFs with a higher financing capacity and a stronger focus on internationalization (Eckey and Memmel, 2022), as well as a high level of innovation before a crisis (Lepp€ aaho and Ritala, 2022), are better able to cope with the challenges of pandemics.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations